Pengaruh Penggunaan Permainan Lompat Ubin Terhadap Hasil Belajar Matematika Materi Konsep Dasar Perkalian Pada Siswa Kelas II B SDK 143 Bhaktyarsa Maumere - Fransiska Erni; Maria Herliyani Dua Bunga; Yohanes Ehe Lawotan (Journal on Education, 2023)
This research was conducted based on the following problem how to influence the use of tile jumping games on the mathematics learning outcomes of the multiplication basic concept material in class II b students at SDK 143 Bhaktyarsa Maumere. in class II b SDK 143 Bhakhtyarsa Maumere. This research uses a type of quantitative research to examine the effect of using the tile jumping game on mathematics learning outcomes on the basic concept of multiplication in class II b SDK 143 Bhaktyarsa Maumere students with a total of 27 students consisting of boys 11 boys and 16 girls. The data were collected using an essay test. The collected data were analyzed using the SPSS 16 application. The results of this study showed that there were significant differences in learning outcomes in mathematics using the tile jump game and the learning model. conventional wisdom. The average score of students' science learning outcomes taught by the tile jumping game is 88 which is classified as very high criteria. The average science learning outcomes of students who are taught by the conventional model is 58 which is in the low category, and tcount = 9.098 t table = 2.056 at a significant level of 5%. This means that t count>t table. So the tile jumping game has a positive effect on the mathematics learning outcomes of class II b SDK 143 Bhaktyarsa Maumere